Concept and Procedures for the Distribution of Joint Inheritance for Heirs of Classes I, II, and III According to the Civil Code (Burgerlijk Wetboek) - Geri Pratama Andika; Imam Kurniawan; Perwira Al Arasy; Osama Pangestu; Mhd Rafli Afrilianda Saragih (Jurnal Cendikia ISNU SU, 2025)
This study discusses the concept and procedures for inheritance distribution based on the rules in the Civil Code (BW) (Burgerlijk Wetboek), specifically the distribution involving heirs from classes 1, 2, and 3 simultaneously. The Civil Code regulates inheritance distribution in stages based on close blood relations to ensure fairness in the distribution of inherited assets. However, in practice, inheritance distribution often faces complexities due to the presence of heirs from different classes, the influence of wills or gifts, and conflicts between heirs. This study uses a qualitative approach with descriptive analysis to explore these issues. The results show that the main complexities lie in the differences in rights among heirs within one class, the simultaneous presence of heirs from different classes, and administrative and document constraints. Family conflicts often exacerbate the situation, requiring mediation or legal settlement to achieve justice. As solutions, the involvement of notaries, document digitization, increasing legal literacy, and mediation are identified as effective steps to overcome these challenges. This study provides insight into the importance of alignment with the Civil Code (BW) in ensuring legal certainty and justice in inheritance distribution.